Förderung von Argumentationskompetenzen auf der Grundlage von Forscheraufgaben: Eine empirische Studie im Mathematikunterricht der Grundschule (mathematica didactica, 2012)
Based on a critical analysis of the term argumentation in the following article an argumentation competence model as well as a teaching concept for the improvement of argumentation skills will be developed. The teaching concept is based on so called “Forscheraufgaben” and the especially for these study developed “4-Phasen-Unterrichtsmodell”. Furthermore an empiric study which was done for a period of 4 month will be presented, in which the teaching concept was evaluated and the competence model was used. One of the results of the study is to show how the requirements of written argumentations are fulfilled by children.